Assessment of Usability of Web-Based Applications' User Interfaces - Mohamed, Ali Mohamed Ali (2017)
A Master of Science thesis in Computer Engineering by Ali Mohamed Ali Mohamed entitled, "Assessment of Usability of Web-Based Applications' User Interfaces," submitted in May 2017. Thesis advisor is Dr. Tarik Ozkul. Soft and hard copy available.